2015
DOI: 10.1155/2015/232401
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Blood Gas Analysis and the Outcome of Treatment in Tricyclic Antidepressants Poisoned Patients with Benzodiazepine Coingestion

Abstract: Background. Poisoning with tricyclic antidepressants (TCAs) is still a major concern for emergency physicians and intensivists. Concomitant ingestion of other psychoactive drugs especially benzodiazepines with TCAs may make this clinical situation more complex. This study aimed to compare the arterial blood gas (ABG) values and the outcome of treatment in patients with coingestion of TCA and benzodiazepine (TCA + BZD) poisoning and TCA poisoning alone. Methods. In this cross-sectional study which was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…In the current study, the age of the studied cases ranged from 16 to 70 years with a mean of 25.4 ± 9.8.0. This was nearly similar to the mean age reported by Yaraghi et al (2015) and Eizadi-Mood et al (2016). The majority of cases were females (89%), from urban areas (72.5%) and were unemployed (49.5%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, the age of the studied cases ranged from 16 to 70 years with a mean of 25.4 ± 9.8.0. This was nearly similar to the mean age reported by Yaraghi et al (2015) and Eizadi-Mood et al (2016). The majority of cases were females (89%), from urban areas (72.5%) and were unemployed (49.5%).…”
Section: Discussionsupporting
confidence: 91%
“…The mean systolic and diastolic blood pressure were 117.5± 17.8 and 74.4± 12.8 respectively. This was nearly similar to mean systolic and diastolic blood pressure of Yaraghi et al (2015) study (107.8± 17.4 and 71.4± 12.5 respectively) and of Avci et al (2020) study (116.4± 12.4 and 71.8± 8.5 respectively). Hypotension was recorded in only 4.6% of cases of the present study while it was reported in 15% of cases of Saleh et al (2013) study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, our subjects who were younger than 20 years of age demonstrated a respiratory acidosis condition on admission. In one study, Arterial Blood Gas (ABG) parameters in patients with Benzodiazepine (BZD) poisoning were measured and the mean pH level was significantly lower than that in patients with TCA poisoning [ 27 ]. It is known that rapid Na+ channel blockade in the heart is sensitive to arterial blood pH, thus acidosis can aggravate cardiovascular toxicity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies on the effects of intoxication with antidepressants or antipsychotics alone in the outcome of the patients. [ 4 5 6 7 8 9 10 ] In this study, we evaluated the predicting factors for the outcome of the patients intoxicated with antidepressants, antipsychotics, and their combination with and without other drugs as no study reported yet.…”
Section: Introductionmentioning
confidence: 99%